Anticoagulation Following Mitral Valve Repair - Watt, Tessa M. F. (J Card Surg, 2020)
BACKGROUND AND AIM: Anticoagulation after mitral valve repair is controversial and guidelines are not well-established. This study evaluated the association between postoperative warfarin use and complications after mitral valve repair, including bleeding and thromboembolic incidents, readmission, and mortality. METHODS: This retrospective study investigated 1097 patients who underwent elective mitral valve repair between April 2003 and March 2017, and were naïve to atrial fibrillation or prior cardiac surgery. This cohort had no other indication for or against anticoagulation. 775 patients were placed on warfarin with INR goal 2.5, and 322 patients were not anticoagulated. The association between anticoagulation and complications was assessed with univariate comparisons between groups and multiple logistic regression. RESULTS: Postoperative warfarin use was associated with a reduced composite of bleeding and thromboembolic complications (pulmonary embolism, TIA, stroke, pericardial effusion or cardiac tamponade, GI bleeding, and reoperation for bleeding) with an odds ratio of 0.29 (95% CI 0.13–0.64, p=0.003). There was no difference in 30-day or 6-month mortality or readmission rate between groups. Long-term survival estimates were superior in the warfarin group (10-year: 92% vs. 85%; log-rank p<0.001). CONCLUSIONS: Our analysis showed that postoperative warfarin use was associated with an overall reduced composite of bleeding and thromboembolic incidents and superior long-term survival. These findings suggest that anticoagulation with warfarin following mitral valve repair may be a safe and effective means for avoiding postoperative complications, and that a large prospective randomized clinical trial is warranted.